Anatomic Variations of the Shape of the Menisci: A Neonatal Cadaver Study - Cetiner Kale, A.; Kopuz, C.; Edýzer, M.; Aydin, M.E.; Demýr, M.; Ýnce, Y. (Springer, 2006)
Meniscal injuries in children and adolescents are being seen with increased frequency. The menisci are two crescentic lamellae whose functions are to deepen the articular surfaces of the tibial plateu for reception of the condyles of the femur. In our study, our aim is to determine the variations of the shapes and attachments of the menisci in newborns. This study was performed on 11 neonatal cadavers, 22 knee joints that were obtained from the anatomy laboratory. The variations of the shape of the menisci were noted. We found that 77% of the lateral menisci were discoid. This percent is higher than the previously reported percents of the lateral discoid menisci. The different shapes of the menisci were determined as horse shoe, sickle, sided U, sided V and C shaped. We did not determine any discoid medial menisci. We believe that our study will provide support to the neonatal anatomy of the knee, concerning with the surgical procedures and arthroscopy of the knee joint. © Springer-Verlag 2006.
Keywords: Knee; Meniscus; Newborn; Shape; Variation